3D printed food system development based on nanoencapsulated and micro powder nutritious ingredients - Mejía-Vásquez, Hernán-Darío; Hernández-Sandoval, Gustavo-Rafael (Revista Colombiana de Investigaciones Agroindustriales, 2021)
The products developed are mainly based on the mixture of powdered food ingredients obtained through the spry dry technology that together with a liquid ingredient form a homogeneous mixture reaches a fluidity behavior inside the printer cartridge during the extrusion process, the deposited or extruded material must present a good balance between fluidity and rigidity to support the load of the deposited layers, thus presenting a structurally stable print. Subsequently, production cost studies of the products were carried out and sensory and rheological analyses were performed.